Exploring income diversification strategies for rural households across three selected agro-ecological zones in the Dawuro Zone, southwestern Ethiopia - Teshome Kassahun Gebeyehu; Girma Gezimu Gebre; Aneteneh Ashebir (Discover Sustainability)
Abstract This paper investigates income diversification and its determinants among rural households via data collected from 203 rural households located in lowland, midland, and highland agro-ecological zones in Ethiopia. A multistage sampling procedure was employed to select sample households. The study utilized primary data, which are qualitative and quantitative in nature. The collected data were analyzed via descriptive statistics and a two-limit Tobit model. To estimate the degree of income diversification among rural households, the Simpson index of diversity was used in this study. The results indicate that the degree of income diversification significantly varied among the rural households in the study area. These variations were explained mainly by differences in resource availability and farmers living in agro-ecological zones. Compared with lowlands, farm households located in highlands and midlands agro-ecological zones had a greater degree of income diversification in the study area. Moreover, the gender of the household head (male), the education level, and the possession of draught power were negatively correlated with the degree of income diversification in the study area, whereas agro-ecological zones, livestock possession, local leadership participation, participation in agricultural extension programs and access to credit services were positively correlated with income diversification. Thus, rural households’ income diversification strategies should be promoted through more investment in pull factors in lowlands rather than in highland and midland agro-ecological zones.